Makna Simbol Komunikasi pada Tarian Barong Brutuk yang Terdapat di Desa Trunyan, Kecamatan Kintamani, Kabupaten Bangli - Indah Yuliarsini, Luh Putu; Alit Suryawati, I Gusti Agung; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2021)
Costumes, properties, and dance styles are so-called forms of non-verbal communication that contain meaningful symbol in each aspect. This subject can be seen from a traditional dance in Bali, Barong Brutuk Dance  This research itself is aimed to comprehend the communication symbol that the dance holds. Barong Brutuk dance is chosen as the main subject of this study due to its peculiar meaning as well as values that Balinese from Trunyan. This research is condoned with the descriptive qualitative method that relies on Roland Barthes’s Semiotic theory. The result of this study that non-verbal communication is carried out throughout each move, costume, and property used in this dance. This dance manifests deeper meaning, some believe that it brings prosperity to the people of Desa Trunyan. From the costumes being worn by the elected carrier or the dancer, they deliver simplicity, and the properties shown displays a symbol of neutralized negativity Keywords : The Meaning of communication symbol, Semiotic, Barong Brutuk Dance.